2020
DOI: 10.34067/kid.0000532020
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Recognition of Chronic Kidney Disease in VA Health Care System Primary Care Clinics

Abstract: BackgroundThe successful implementation of interventions targeted to improve kidney health requires early identification of CKD which involves screening at-risk populations as well as recognizing CKD. We aim to determine CKD screening and recognition rates, factors associated with these rates, and evaluate the effect of CKD awareness on delivery of care.MethodsA retrospective cohort study of veterans enrolled with Veterans Integrated Service Network 17 who had hypertension (HTN) and/or diabetes (DM) and were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…While early diagnosis is critical, appropriate medical treatment is necessary to slow disease progression. Studies have similarly found low rates of CKD recognition despite high rates of screening [ 39 42 ] and targeted intervention to improve CKD awareness and treatment [ 43 45 ], indicating that CKD awareness alone may not be sufficient to improve appropriate medical management.…”
Section: Discussionmentioning
confidence: 99%
“…While early diagnosis is critical, appropriate medical treatment is necessary to slow disease progression. Studies have similarly found low rates of CKD recognition despite high rates of screening [ 39 42 ] and targeted intervention to improve CKD awareness and treatment [ 43 45 ], indicating that CKD awareness alone may not be sufficient to improve appropriate medical management.…”
Section: Discussionmentioning
confidence: 99%
“…While early diagnosis is critical, appropriate medical treatment is necessary to slow disease progression. Studies have similarly found low rates of CKD recognition despite high rates of screening [39][40][41][42] and targeted intervention to improve CKD awareness and treatment [43][44][45] , indicating that CKD awareness alone may not be su cient to improve appropriate medical management.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of these models is to allow for earlier detection of, and thereby intervention for, CKD. CKD awareness remains low relative to other chronic diseases such as diabetes which results in low rates of appropriate testing (e.g., UACR) [33,34]. This, in turn, leads to under-prescription of preventive medications well proven to slow progression (e.g., angiontesin converting enzyme inhibitors/angiontesin receptor blocker, SGLT2 inhibitors).…”
Section: Prediction Of Earlier Kidney Outcomesmentioning
confidence: 99%